The representation of linguistic variations in the speech by Chico Bento, by Mauricio de Sousa (Research, Society and Development, 2022)
It is known that linguistic variations are intrinsic phenomena to languages, and that it is a process resulting from the diversity and constitution of human communities. Therefore, the present work has as general objective to analyze the linguistic variety in the speech of the character Chico Bento, in the strips of Maurício de Sousa, in addition to discussing linguistic prejudice and how the teacher can act in the classroom. This debate is important in all social spaces, especially in the school environment, since linguistic varieties are present in the mother tongue, in the most varied spaces and contexts. This bibliographic work analyzed the linguistic varieties present in Chico Bento's. Chico Bento's speech was chosen because it presents the diatopic variation, a colloquial language typical of the rural area, in which “lh” is exchanged for “i”. It was found that working on linguistic variation in the classroom is a fundamental role of the Portuguese language teacher, because, in this way, it allows the student to reflect on the differentiated use that should be made of the language in certain situations.